Atmospheric Boundary Layer Processes: Impacts on Weather Patterns and Climate Change - Shreya Singh (International Journal of Atmosphere, 2024)
The atmospheric boundary layer (ABL) is a vital component of the Earth's climate system, acting as the interface between the terrestrial surface and the overlying atmosphere. This layer, typically extending from the surface to a height of a few hundred meters, is characterized by strong gradients in meteorological variables such as temperature, humidity, wind speed, and atmospheric pressure. Understanding the dynamics of the ABL is essential for comprehending weather phenomena, climate variability, and the dispersion of pollutants.This review delves into the intricacies of the planetary boundary layer (PBL) and surface layer, which constitute the two primary components of the ABL. The PBL is influenced by larger-scale atmospheric processes and is marked by turbulence generated through surface friction and thermal instability. In contrast, the surface layer, situated closest to the Earth’s surface, experiences significant interactions with the land or ocean, playing a crucial role in the exchange of energy and momentum.One of the key focuses of this review is the interaction between air-sea and land-atmosphere systems. These interactions are critical for the transfer of energy and momentum, impacting local weather patterns and climate dynamics. Surface roughness, which varies depending on the type of terrain (urban, forested, or agricultural), significantly influences the flow of air within the boundary layer. This variability affects turbulence intensity, which in turn modulates the mixing of heat and moisture.The significance of scalar transfer within the ABL cannot be overstated. Heat flux, water vapor flux, and carbon dioxide flux are critical components that dictate local climate conditions and ecosystem health. These fluxes result from both atmospheric processes and land surface characteristics, highlighting the intricate link between the biosphere and the atmosphere. Trace gas exchanges are also essential, as they influence the atmospheric composition and contribute to greenhouse gas concentrations, affecting global warming.The review further explores the impact of air pollution dispersion within the boundary layer. Urban areas, which are often characterized by elevated emissions, face unique challenges in pollutant management. The dispersion of pollutants is influenced by boundary layer dynamics, including stability conditions and turbulence. Understanding these dynamics is crucial for developing effective air quality management strategies and for mitigating the health impacts of air pollution.Additionally, the characteristics of stable and convective boundary layers are discussed, as they exhibit distinct behaviors that influence meteorological phenomena. Stable boundary layers are typically associated with clear skies and calm conditions, while convective boundary layers arise during daytime heating, resulting in vertical mixing and enhanced turbulence.This comprehensive overview underscores the importance of boundary layer parameterization in improving climate models and forecasting systems. Accurate representation of the ABL in numerical weather prediction models is essential for reliable weather forecasts and climate projections. As climate change alters the dynamics of the ABL, ongoing research is crucial to enhance our understanding and improve predictive capabilities.In summary, the ABL is a dynamic and complex system with significant implications for weather, climate, and air quality. This review highlights the need for further research to deepen our understanding of the ABL's processes and interactions, ensuring that we can effectively address the challenges posed by climate change and environmental degradation.